2013
DOI: 10.1113/expphysiol.2012.070037
|View full text |Cite
|
Sign up to set email alerts
|

The C57Bl/6 mouse serves as a suitable model of human skeletal muscle mitochondrial function

Abstract: New Findings r What is the central question of this study?Do mouse skeletal muscle mitochondria resemble human skeletal muscle mitochondria sufficiently to serve as a proper model and how do differences of skeletal muscle type affect the comparison? r What is the main finding and its importance?We find that mouse skeletal muscle respiratory capacity and control function rather similar to human m. vastus lateralis, with the mouse quadricep being overall the most similar. This resemblance is not universal, howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
44
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 72 publications
5
44
0
Order By: Relevance
“…Enzymatic activity of citrate synthase (CS) has been used as a biomarker of mitochondrial content (Larsen et al, 2012) and function (Jacobs et al, 2013) in skeletal muscle. It has been known that endurance exercise training leads to an increase in CS activity in exercised skeletal muscles (Holloszy and Booth, 1976).…”
Section: Discussionmentioning
confidence: 99%
“…Enzymatic activity of citrate synthase (CS) has been used as a biomarker of mitochondrial content (Larsen et al, 2012) and function (Jacobs et al, 2013) in skeletal muscle. It has been known that endurance exercise training leads to an increase in CS activity in exercised skeletal muscles (Holloszy and Booth, 1976).…”
Section: Discussionmentioning
confidence: 99%
“…A direct comparison of the respiratory results gained from the human vastus lateralis muscle and the murine soleus muscle is therefore not possible. It has previously been shown that mitochondrial respiration differs between murine soleus muscle compared to the murine quadriceps and gastrocnemius muscle [49]. Furthermore, the murine quadriceps muscle has been shown to be a suitable model for the human skeletal muscle [49].…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been shown that mitochondrial respiration differs between murine soleus muscle compared to the murine quadriceps and gastrocnemius muscle [49]. Furthermore, the murine quadriceps muscle has been shown to be a suitable model for the human skeletal muscle [49]. Due to the high mitochondrial mass of the soleus muscle the respiratory values depend on the mitochondrial content, which should be considered for analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Soleus muscles were rapidly excised from isoflurane anesthetized mice and immediately placed in ice-cold biopsy preservation medium processed as described here [42]. Briefly, muscle samples were gently dissected with a pair of fine-tipped forceps and separated fibers were permeabilized with saponin (50 µg/ml) for 30 min at 4°C [43].…”
Section: Methodsmentioning
confidence: 99%